2012
DOI: 10.1080/1389224x.2012.670053
|View full text |Cite
|
Sign up to set email alerts
|

Local Farmers' Organisations: A Space for Peer-to-Peer Learning? The Case of Milk Collection Cooperatives in Morocco

Abstract: The study investigated to what extent local farmers' organisations are spaces where farmers discuss, learn, and innovate. Design/methodology/approach. Two milk collection cooperatives in Morocco were studied. The study analysed the discussion networks, their impacts on farmers' knowledge and innovation, and the performance of collective action at cooperative level. Findings. In both cooperatives, only two-thirds of the farmers regularly discussed dairy practices with other farmers. Most leaders of one cooperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Cases of low density and reciprocity associated with collective action failure are reported in the literature. For example, Faysse et al [11] studied two dairy cooperatives in Morocco with 180 and 140 members, respectively, and found that the first had a very low density (0.35%) with two reciprocal links, and the second had a density of 0.56% with one reciprocal link. Pachoud et al [8] showed that the advice network of 46 producer members of an association for the protection of Serrano cheese in southern Brazil had a density of only 2% and there was no reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of low density and reciprocity associated with collective action failure are reported in the literature. For example, Faysse et al [11] studied two dairy cooperatives in Morocco with 180 and 140 members, respectively, and found that the first had a very low density (0.35%) with two reciprocal links, and the second had a density of 0.56% with one reciprocal link. Pachoud et al [8] showed that the advice network of 46 producer members of an association for the protection of Serrano cheese in southern Brazil had a density of only 2% and there was no reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that farmers may be more readily engaged in initiatives that share welfare practices and knowledge from farmer to farmer. This is supported by the results of another study that found that farmers' involvement in active peer dialogue networks to be improved their capacity to innovate [ 17 ].…”
Section: Discussionmentioning
confidence: 62%
“…The P2PL approach (Shiner 1999;Eisen 2001) is nowadays adopted in several fields of adult education as well as in agroenvironmental extension (cf. Faysse, Sraïri, and Errahj 2012). Even though the importance of peer forest owners in information delivery has already been highlighted by West et al (1988), forest owners' P2PL were not studied until the past decade in the US (e.g.…”
Section: Change In Forest Owners' Profiles -A Catalyst For Rethinkingmentioning
confidence: 99%